Surfactant from candida tropicalis grown on soya water-copra meal and rice washing-ammonium phosphate - Gjenilynne F. Mandigma. 4 0 16; 5 (2003)
u
Thesis: (Bachelor of Science in Chemistry) - Pamantasan ng Lungsod ng Maynila, 2003.
Keywords: 2 -- 0; 6; 20; 20; 2